2022
DOI: 10.15252/embr.202154133
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of TRAIL triggers degranulation and IFNγ production in human natural killer cells

Abstract: NK cells utilize a large array of receptors to screen their surroundings for aberrant or virus‐infected cells. Given the vast diversity of receptors expressed on NK cells we seek to identify receptors involved in the recognition of HIV‐1‐infected cells. By combining an unbiased large‐scale screening approach with a functional assay, we identify TRAIL to be associated with NK cell degranulation against HIV‐1‐infected target cells. Further investigating the underlying mechanisms, we demonstrate that TRAIL is abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 85 publications
3
8
0
Order By: Relevance
“…Notably, expression of GABBR1 ( gamma aminobutyric acid type B receptor 1 ), which our group has recently shown to oppose CaSR-mediated calcium sensing in the parathyroid ( 34 ), is significantly elevated in Def-Ts. Additional genes found to be significantly upregulated in these tumors act in signaling pathways controlling apoptosis (TNFSF10, tumor necrosis superfamily member 10 ) ( 35 , 36 ), cellular stress response (SGK1, serum glucocorticoid regulated kinase 1 ) ( 37 ), inositol-derived second messenger production (IPMK, inositol polyphosphate multikinase ) ( 38 ), and energetic metabolism (AMPD3, adenosine monophosphate deaminase 3 ) ( 39 ). Despite the higher preoperative PTH observed in vitamin D-deficient PHPT patients, PTH transcript abundance was not significantly different between tissue sources ( P = 0.2862 by one-way ANOVA) or when comparing chief to oxyphil cells ( P = 0.7284 by unpaired t -test).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, expression of GABBR1 ( gamma aminobutyric acid type B receptor 1 ), which our group has recently shown to oppose CaSR-mediated calcium sensing in the parathyroid ( 34 ), is significantly elevated in Def-Ts. Additional genes found to be significantly upregulated in these tumors act in signaling pathways controlling apoptosis (TNFSF10, tumor necrosis superfamily member 10 ) ( 35 , 36 ), cellular stress response (SGK1, serum glucocorticoid regulated kinase 1 ) ( 37 ), inositol-derived second messenger production (IPMK, inositol polyphosphate multikinase ) ( 38 ), and energetic metabolism (AMPD3, adenosine monophosphate deaminase 3 ) ( 39 ). Despite the higher preoperative PTH observed in vitamin D-deficient PHPT patients, PTH transcript abundance was not significantly different between tissue sources ( P = 0.2862 by one-way ANOVA) or when comparing chief to oxyphil cells ( P = 0.7284 by unpaired t -test).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have confirmed that NK cells may improve immunity via inducing degranulation via TRAIL. 52 Hence, it is reasonable that the changes we observed in CAR-iNK cells might contribute to NK-cell-mediated cytotoxicity.…”
Section: Discussionmentioning
confidence: 77%
“…In cSCC (Figure 3C and Table S7), a relatively consistent trend for an upregulation of cluster unique genes that enhancing NK cell activation or expansion were detected in C0 (CD2, CD52) 61,62 , C1 (NCR3, OASL, NFKBIZ, TSC22D4) 63,64 , C2 (KLRC3, IKZF3, ETS1, NFIL3, JAK1, NKTR) 65,66 , and C4 (GNLY, TNFSF10) 67 , and a downregulation of immunosuppressive genes were concertedly detected in C0 (USP14) 68 , C1 (TNFRSF18, HLA-B, HLA-C) [69][70][71] , and C4 (IKZF2, LAG3, KIR2DL1) 30 , consistent with the elevated NK cell activation signatures in all NK cell clusters from the tumor of SCC. (Figure 2D).…”
Section: Unique Characteristics For Each Nk Cell Cluster In Skin Cancersmentioning
confidence: 77%